Emerging therapies for the treatment of uveitis: clinical trial observations. (October 2013) - Metzinger, Jamie Lynne; Foster, C Stephen
Uveitis, a leading cause of blindness in the USA and western Europe, can pose a challenge to ophthalmologists when considering treatment modality. Although once considered acceptable, corticosteroid monotherapy is no longer alone at the head of treatment options. Newer, more specific treatments, and medications translated from other divisions of medicine comprise the new wave of therapy employed by uveitis practitioners around the world, with and without regulatory approval. The purpose of this review is to examine the current status of clinical trial observations for newer treatments for uveitis. Innovative corticosteroid therapies and methods of delivery are described, in addition to novel calcineurin inhibitors, new biologic response modifiers, and other emerging therapies. Although very few therapies are approved for use explicitly in uveitis, the reported results of clinical trials are examined. A concise overview of the ongoing challenges in clinical research is discussed, from the perspective of the uveitis specialist, and the patient. Direction for the future of drug development and use is both exciting and dire, as these treatments are the only pathway for patients seeking to preserve vision.